Enter the Ring: Artistic Interventions in Facial Recognition and Domestic Surveillance - Fahner, Craig; Light, Evan; MacNeil, Quinn (Surveillance & Society)

(untitled) (Surveillance Studies Network, 2026)
The use of domestic surveillance products such as Amazon’s Ring doorbell system has, in recent years, become widespread. While the fisheye lenses and glowing blue LED buttons of Ring doorbells have become familiar sights on doorsteps in North America and beyond, little information is presented to end users regarding Ring’s relationships with police agencies and data brokers, and, perhaps most significantly, its deployment of emerging facial recognition technologies. This paper examines the emergence of the Ring doorbell and similar home security products, attempting to unravel the possibilities and dangers of the increasing implementation of facial recognition technologies in domestic and public space. We deploy a research-creation method to bring these possibilities and risks to the fore. Our interactive exhibition Enter the Ring seeks to invert the information asymmetry held by the proprietors of proprietary domestic surveillance platforms: where Amazon and other businesses conceal the myriad ways that their video surveillance products quantify individuals and draw inferences from human faces, our installation instead serves as a mirror that reveals to the audience the extent to which these techniques can be deployed to make predictions as to an individual’s identity and, ultimately, whether they might be deemed risky or safe. We argue that this kind of artistic intervention using interactive media serves a crucial role in bridging the information gap around facial recognition technologies and may be used to benefit both public education and regulatory action regarding algorithmic surveillance.